GAMBARAN PENERAPAN PERILAKU ETIK PERAWAT SESAMA SEJAWAT DI RUANG ICU RUMAH SAKIT LABUANG BAJI - imran pashar; Sardi Anto; Juhelnita Bubun (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Nurses need professional competence and a framework provided by a code of ethics as service standards and correct judgment while working with colleagues. This is done to prevent misunderstandings and conflicts from occurring. The purpose of this study was to describe the application of ethical behavior among colleagues in the ICU room of Laburan Baji Hospital. The type of research used in this research is a non-experimental quantitative research with a descriptive research design. The sampling technique uses Total Sampling. The sample in this study were 30 people as respondents. The instrument in this study used a questionnaire. The results of the study showed that the communication of nurses with other nurses in the ICU room of Laburan Baji Hospital, the majority of respondents communicating with other nurses were in the very good category with 17 respondents (56.67%), then the actions of nurses to other nurses in the ICU room of the Hospital Most of the respondents in the relationship between nurses and other nurses were in the very good category, 15 respondents (50%), while the nurses' responsibilities to other nurses in the ICU room of Laburan Baji Hospital, most of the respondents' responsibilities to other nurses were in the very category. good as many as 19 respondents (63.33%). In conclusion, most of the ethical behavior of fellow nurses is in the very good category. It is hoped that in this research nurses can apply ethical behavior among colleagues so as to create harmonious relationships and prevent conflict